Recent Advances on Sodium‐Ion Batteries and Sodium Dual‐Ion Batteries: State‐of‐the‐Art Na+ Host Anode Materials. Issue 6 (5th May 2021) - Gong, Decai; Wei, Chenyang; Liang, Zhongwang; Tang, Yongbing
Abstract : Sodium is abundant on Earth and has similar chemical properties to lithium, thus sodium‐ion batteries (SIBs) have been considered as one of the most promising alternative energy storage systems to lithium‐ion batteries (LIBs). Meanwhile, a new energy storage device called sodium dual‐ion batteries (SDIBs) is attracting much attention due to its high voltage platform, low production cost, and environmental benignity coming from the feature of directly using graphite as the cathode. However, due to the large mass and ionic radius of sodium atoms, SIBs and SDIBs exhibit low energy density and inferior cycling life than LIBs. Over the past few years, tremendous efforts, especially in the area of anode materials, have been made to improve the electrochemical performance of SIBs and SDIBs. Reviewing and summarizing the previous studies will be helpful for future exploration and optimization. Herein, the recent progress on anode materials for SIBs and SDIBs is summarized according to the reaction mechanism. The structural design, reaction mechanism, and electrochemical performance of the anode materials are briefly discussed. In addition, the fundamental challenges, potential solutions, and perspectives in this field are also proposed. It is hoped that this Review may advance the development of anode materials for sodium storage. Abstract : The recent progress on anode materials for both sodium‐ion batteries and sodium dual‐ion batteries are summarized according to the different sodium storage mechanisms. The structural design, reaction mechanism, and electrochemical performance of the anode materials are briefly discussed. In addition, the fundamental challenges, potential solutions, and perspectives in this field are also presented.